The 1996 Zambia National Housing Policy - Makasa, Paul.; IOS Press (Amsterdam : IOS Press, 2010)
Devising a workable housing policy in a country with apparently insurmountable housing problems, presents a great challenge. With the help of an award from UN-HABITAT, Zambian authorities attempted to do just this, in a process which is an ideal candidate for scrutiny. This study analyzes the goals, means and instruments that were used to formulate the policy, as well as its planned implementation. It examines whether the policy could have achieved its goals had it been implemented, and represents a valuable addition to the body of knowledge which can help to evaluate the potential for success.
Title page; Contents; Acknowledgements; Background to the research problem; Background and context of the study area; Conceptual and theoretical frameworks; The 1996 'award winning' Zambia National Housing Policy; The genesis of Zambia's urban and housing problems; Critical analysis of the 1996 National Housing Policy; Quantifying the housing need; Towards a new paradigm in housing policy formulation and implementation; Conclusions and recommendations; Postscriptum: the BBC/UN-HABITAT World Debate on Housing; References; Appendix 1. Densification stages in Lusaka.
Includes bibliographical references.
Print version record.
eBooks on EBSCOhost
Keywords: Housing policy -- Zambia; Architecture and state -- Zambia; Logement -- Politique gouvernementale -- Zambie; Architecture -- Politique gouvernementale -- Zambie; SOCIAL SCIENCE -- General; BUSINESS & ECONOMICS -- Infrastructure; Architecture and state; Housing policy; Zambia; dissertations; Academic theses; Academic theses; Thèses et écrits académiques.